Pengaruh Disiplin Kerja, Pengalaman Kerja, Kecerdasan Emosional Pimpinan dan Pengawasan terhadap Kinerja Sdm PT. KAI (Persero) Daop 4 Semarang - Purnomo Ari Wibowo; Sugeng Hariyanto (OPTIMAL Jurnal Ekonomi dan Manajemen, 2025)
The success of an organization is generally reflected in its overall performance, which demonstrates the effectiveness of achieving organizational goals. Organizational performance is closely linked to the role of human resources, as people are one of the most valuable assets within an organization. Leadership is a critical factor in guiding and helping organizations reach their objectives. A leader’s ability to improve the performance of their subordinates is key to organizational success. One essential trait of effective leaders is high emotional intelligence, which includes emotional awareness, self-management, motivation, empathy, and social skills. Emotional intelligence enables leaders to enhance productivity and success by effectively managing their emotions and interactions with others. It also helps subordinates become more productive, thereby improving overall employee performance. By fostering these emotional skills, a leader can build a more harmonious and effective working environment that aligns with organizational goals and drives success.